PENGARUH PENGALAMAN AUDIT, PENGETAHUAN MENDETEKSI KEKELIRUAN, INDEPENDENSI DAN AUDIT TENURE PADA AUDIT JUDGMENT - Oktaviana, Made Ayu; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi, 2018)
The purpose of this research was to obtain empirical evidence on the influence of audit experience, knowledge of detecting errors, independence and audit tenure on audit judgment. This research was conducted at Public Accountant Office in Bali area and registered in IAPI year 2017 with primary data collection method that is questioner. The number of samples analyzed by 44 respondents, and using purposive sampling method. The analysis technique used is Multiple Linear Regression Analysis. The final result of the research states that the higher the audit experience the more accurate audit judgment. Increasing the knowledge detecting errors an auditer so audit judgment is more accurate. The higher the independence of an auditor the audit judgment is more accurate. The more audit tenure an auditer the audit judgment more accurate.